Methods for Assessing the Credit Risk of Leasing Assets - Asyaeva, Elmira A.; Chizhankova, Inna V.; Bondaletova, Natalia F.; Makushkin, Sergey A. (International Journal of Economics and Financial Issues, 2016)
This paper analyzes how to appeal to the securitization of leasing companies affect the possible appearance in Russia in the framework of Basel II and Basel III capital requirements in respect of credit risk operations, securitization of leasing assets. It also discusses the possible implications for lessors, planned to carry out securitization during the implementation of the project in the Russian document “Updates to the framework agreement of the Basel Committee approach to securitization” in its current wording. Keywords: credit risk, assessment methodology, leasing assets JEL Classifications: D80, G32